PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, DISIPLIN KERJA MOTIVASI DAN INSENTF TERHADAP KINERJA KARYAWAN KOPERASI SIMPAN PINJAM RUKUN IKU AGAWAE SANTOSO - BELLY OKTA WIJAYA (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
Research was conducted on Credit Unions Rukun Iku Agawe Santoso which aims to determine the effect of leadership style, work environment, work discipline, motivation and incentives on employee performance. This research was conducted on the employees of Koperasi Simpan Pinjam Rukun Iku Agawe Santoso P1 Mardiharjo with members of the sample of 80 respondents, the sampling technique used saruration sampling methods and research instruments were a questionnaire with Likert scale 1-5. The analytical method used is multiple linear regression analysis with the data that has met the validity, reliability, and classical assumption. Hypothesis testing using t partially shows that the independent variable is the discipline of work to significantly affect the dependent variable employee performance. As for the variables of leadership style, work environment, motivation and incentives do not affect the performance of employees. Figures Adjusted R Square .204, showed that 20.4% of employee performance variation can be explained by five independent variables in the regression equation. While the remaining 79.6% is explained by other variables outside variables used in this study.